Notes to Philosophy 167: Class 8 -- Descartes' Principia: Laws of Motion -- Part 5 - Part 6. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Descartes' Intellectual Mission -- The Scope and Goals of Cartesian Science -- The Historical Significance of Cartesian Science -- The Mechanical Philosophy: Two Schools -- Descartes on the Vacuum and Atomism -- The Plenist World View, Versus Ours -- Descartes on Magnetic Phenomena.; Generally corresponds to the video segment: Class 8, Part 5 - 6.